ADVANCING GENDER EQUALITY IN SIERRA LEONE’S LAND SECTOR - Mosugu, Tegan Joseph (European Scientific Journal, ESJ, 2015)
Africa has not been immune of land rights violations. Throughout Africa, the right to use and access land has been obstructed from marginalized communities. Women are the victims of this harsh reality and efforts to address this on a universal level has been futile. As an independent researcher, I conducted a deep-analysis of the literature in order to understand the adaptive challenge of gender equality and the infringement of women’s rights when it comes to land access and use in Sierra Leone. Using an adaptive analysis framework, I was able to comprehend the systemic inequalities and complexities in the land sector, as a result, I was well equipped to provide real-time recommendations for organizations on the ground such as Transparency International. These recommendations provided actors and stakeholders with a set of practical tools so as to be better equipped in their gender empowerment and risk assessment work.